Teachers’ Perceptions on the Implementation of Principal’s Supervision at SMK N 2 Guguak District - Walef, Sri Mures; Nikmatulaili, Nikmatulaili; Marsidin, Sufyarma; Rifma, Rifma (Graduate Program Magister Manajemen Pendidikan, 2023)
The purpose of this study was to obtain information about the teacher’s perception of the process of supervising, aspects of being supervised, techniques used in supervision. The population as well as the research sample were all teachers at SMKN 2 in Guguak District, totaling 52 teachers. The research instrument uses a questionnaire in the form of a Likert scale with five alternative answers: always, often, sometimes, rarely and never. Then the data were analyzed using the average formula (mean). The results showed that the teacher’s perception of the school principal’s supervision process was well implemented where the average score was 3.1. The teacher’s perception of aspects supervised by the principal is also carried out quite well where the average score is 3.1. Furthermore, the teacher’s perception of the supervision technique used is also quite good where the average score is 3.1. In conclusion, the implementation of supervising school principals at SMKN 2 in Guguak District has been carried out quite well.